The colour fantastic : chromatic worlds of silent cinema - Fossati, Giovanna (Framing film., 2018)
Sparked by a groundbreaking Amsterdam workshop titled 'Disorderly Order': Colours in Silent Film, scholarly and archival interest in colour as a crucial aspect of film form, technology and aesthetics has enjoyed a resurgence in the past twenty years. In the spirit of the workshop, this anthology brings together international experts to explore a diverse range of themes that they hope will inspire the next twenty years of research on colour in silent film. Taking an interdisciplinary approach, the book explores archival restoration, colour film technology, colour theory, and experimental film alongside beautifully saturated images of silent cinema.